IMPROVEMENT OF PRESSURE AND COMPRESSIVE STRAIN SENSING USING PRISTINE CARBON NANOTUBES FOREST. - , MUHAMMAD YASAR (2016)
Carbon nanotubes (CNTs) are considered to be alternative pressure and strain sensing elements, as they present better electromechanical properties that persist to be predictable even at higher temperatures. Till now, pressure and strain sensors based on CNTs have employed polymer in conjunction with different form of CNTs to attain characteristics; such as repeatability, reliability and recoverability. However, the use of polymers restrict the operational temperature range. Whereas, CNTs forest in pristine form tend to buckle permanently in response to compression making it unsuitable for electromechanical sensing. Therefore, it is required to develop CNTs arrays/forest in pristine form to be employed as pressuresensing elements with specific properties; such as mechanical resilience and ability not to buckle permanently upon compression. The development ofelectromechanical transducer would require the synthesis ofthe pristine vertically aligned CNTs arrays/forest which exhibit elasticity.